Microplastics abundance and characteristics in surface waters from the Northwest Pacific, the Bering Sea, and the Chukchi Sea. (June 2019) - Mu, Jingli; Zhang, Shoufeng; Qu, Ling; Jin, Fei; Fang, Chao; Ma, Xindong; Zhang, Weiwei; Wang, Juying
Abstract: Microplastics (MPs) in the Arctic Ocean have gained considerable attention due to its ubiquity and impacts within ecosystems. However, little information is available on MPs in the Pacific section of the Arctic Ocean. The present study determined the abundance, distribution, and composition of MPs in surface waters from the Northwestern Pacific, the Bering Sea, and the Chukchi Sea. The MPs abundances varied from 0.018 items/m 3 to 0.31 items/m 3, with a mean abundance of 0.13 ± 0.11 items/m 3 . The highest level of MPs was found in the Chukchi Sea. Of all of the detected MPs, polyethylene terephthalate (PET) accounted for the largest proportion of MPs, and fiber was predominant with regard to the total amount. Our results highlighted that the Arctic Ocean is becoming a hotspot for plastic pollution, and the risks posed by MPs need to be paid closer attention in future investigations. Graphical abstract: Unlabelled Image Highlights: This study was the first investigation of MPs in waters from the Chukchi Sea. A significant correlation was observed between the abundance of MPs and the latitude. The highest level of MPs was found in the Chukchi Sea. PET accounted for the largest proportion of MPs. The Arctic Ocean is becoming a hotspot for plastic pollution.